Acupuncture for Chronic Central Serous Chorioretinopathy: A Prospective Case Series. Issue 6 (December 2016) - Liang, Zhu; Tian, Chenbin
Objective: The aim of this prospective observational study was to evaluate the effects of acupuncture at Erjian on chronic central serous chorioretinopathy (CSC). Study Design: Prospective case series. Methods: Nine patients with chronic CSC were recruited and each patient received 12 sessions of acupuncture treatment. Subjective symptom measures included complications, best-corrected visual acuity (BCVA), fluorescein leakage (via fluorescein fundus angiography), and central subfield foveal subretinal fluid (on optical coherence tomography (OCT)) at 3 months. Successful treatment was defined as the complete resolution of subretinal fluid observed by the OCT following completion of treatment. Results: After 2 months of treatment, two patients showed improvements in visual acuity, a significant reduction in subretinal fluid and an improvement in BCVA to 0.5±0.10 (mean±SD). By contrast, four patients experienced no significant changes. After 3 months of treatment, four patients showed improvements in visual acuity and complete resolution of the subretinal fluid (mean BCVA=0.6), while parameters in two patients remained unchanged. Compared to baseline (before treatment), the proportions of patients experiencing visual improvement at 2 and 3 months were 33% (n=2) and 67% (n=4), respectively. No major complications were observed during the treatment course. Conclusions: Acupuncture might be a promising supplementary therapy for patients with CSC. However, this is ultimately only an exploratory study with a small sample size and no untreated comparator group to control for the natural history of the condition. Randomised controlled trials will be needed to demonstrate the efficacy and effectiveness of this approach.